Nudix Hydroxylase 15 Mutations Strongly Predict Thiopurine-Induced Leukopenia Across Different Asian Ethnicities: Implications for Screening in a Diverse Population - Khoo, Xin-Hui; Wong, Shin Yee; Ibrahim, Nik Razima Wan; Ng, Ruey Terng; Chew, Kee Seang; Lee, Way Seah; Wong, Zhi Qin; Raja Ali, Raja Affend; Shahrani, Shahreedhan; Leow, Alex Hwong-Ruey; Hilmi, Ida Normiha (Frontiers in Medicine, 2022)
Background and Aims: Thiopurines, which are immunosuppressive drugs for maintaining remission for inflammatory bowel disease, are known to cause myelotoxicity in patients with NUDT15 genetic variants in some Asian countries with monoethnic population. We aimed to investigate the association of NUDT15 variants with leukopenia in a multiethnic population in Southeast Asia. Methods: Patients with a confirmed diagnosis of inflammatory bowel disease were recruited. We collected demographic and clinical characteristics, and whole blood counts before and after initiating thiopurines. TPMT and NUDT15 genotype were analyzed with SNPs genotyping assay. Leukopenia was defined as white cell count < 3000/uL. Results: Nineteen (18.6%) of the 102 patients who had adequate thiopurines therapy experienced leukopenia, 11 (57.9%) have NUDT15 c.415C>T variants, 2 (10.5%) have NUDT15 c.52G>A variants while one (5.3%) have TPMT variation. Individually, NUDT15 c.415C>T had a sensitivity and specificity of 57.9% and 94.0% (OR=21.45, 95% CI 5.94 – 77.41, p<0.001), respectively of predicting thiopurine-induced leukopenia while NUDT15 c.52G>A were only observed in patients with leukopenia. As compared to patients with wildtype NUDT15, both NUDT15 variations had a combined sensitivity and specificity of 68.4% and 94% respectively (OR=33.80, 95% CI 8.99-127.05, p<0.001) of predicting thiopurine-induced leukopenia as well as a shorter onset to leukopenia (median onset [months] 5.5 versus 2.0; p=0.045). Sub-group analysis showed that both NUDT15 variations was strongly associated with leukopenia among the Chinese and Indians but not among the Malays. Conclusion: NUDT15 variants strongly predicted thiopurine-induced leukopenia across a multiethnic Southeast Asian population, particularly among the Chinese and Indians.